Determinan Pencegahan Kecurangan Pengelolaan Dana Desa Dimoderasi Kompetensi Aparatur - Supami Wahyu Setiyowati; Mochamad Fariz Irianto; Irma Tyasari (Universitas Winaya Mukti, 2022)
A quality report is a demand that must be carried out by the village head. A village government that is free from fraud is a government that implements accountability and transparency in every activity. The purpose of village government activities is to improve the village economy. The purpose of this study is to determine the determinants of preventing fraud in village funds in moderating the competence of the apparatus. The research site is in Wajak sub-district, Malang district. The research population is all village officials in Wajak sub-district. The sampling technique used a saturated sample. The research sample is 104 village officials. The data analysis technique uses Smart PLS. The results showed that Fraud prevention, Whistleblowing, and morality had an effect on preventing fraud in village funds. A good control system reduces fraud in the management of village funds. Whistleblowing is behavior that reports fraud and has an impact on reducing fraud in managing village funds. Good morality reduces fraud in village funds. The competence of the apparatus strengthens the relationship between the government's internal control system and morality towards preventing fraud in village funds. The competence of professional apparatus with good morals and good fraud prevention implementation further reduces village fund fraud. The competence of the apparatus has not been able to moderate the relationship between whistleblowing and the prevention of village funds. The implication of this research is that professional officials who have a caring attitude are needed to report anything that deviates from the existing rules.